Development of chromatographic and free radical scavenging activity fingerprints by thin-layer chromatography for selected Salvia species - Cieśla, Łukasz; Staszek, Dorota; Hajnos, Michał; Kowalska, Teresa; Waksmundzka-Hajnos, Monika (Phytochemical analysis, 2011)
Introduction – Plant‐derived free radical scavengers have become the subject of intensive scientific interest. Recently, the concept of coupling chromatographic fingerprints with biological fingerprinting analysis has gained much attention for the quality control of plant extracts. However, identification of free radical scavenging activity of each single compound in a complex mixture is a difficult task. Thin‐layer chromatography with post‐chromatographic derivatisation with the methanol solution of DPPH can be a valuable tool in such analyses. Objective – Development of chromatographic and free radical scavenging fingerprints of nineteen Salvia species grown and cultivated in Poland. Methodology – Chromatography was performed on the silica gel layers with use of two eluents, one for the resolution of the less polar compounds, and the other one for the resolution of the medium and highly polar ones. The plates were sprayed with the vanillin–sulfuric acid reagent to produce chemical fingerprints, and with DPPH solution to generate free radical scavenging fingerprints. Results – With four Salvia species, it was revealed that their strong free radical scavenging properties are not only due to the presence of polar flavonoids and phenolic acids, but also due to the presence of several free radical scavengers in the less polar fraction. Because of the similarities in both the chromatographic and the free radical scavenging fingerprints, S. triloba can be introduced as a possible equivalent of the pharmacopoeial species, S. officinalis. Conclusion – Fingerprints developed in the experiments proved useful for the analysis of complex extracts of the different Salvia species. Copyright © 2010 John Wiley & Sons, Ltd.